2020
DOI: 10.2174/1381612826666200203145851
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants, Health Effects and Bioactive Properties of Wild Allium Species

Abstract: Background: There is an increasing interest from the pharmaceutical and food industry in natural antioxidant and bioactive compounds derived from plants as substitutes for synthetic compounds. The genus Allium is one of the largest genera, with more than 900 species, including important cultivated and wild species, having beneficial health effects. Objective: The present review aims to unravel the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 273 publications
1
14
0
Order By: Relevance
“…The cyclic dithiins are presumed to be the first products of allicin transformation, while acyclic compounds are produced during the thermal degradation of cyclic dithiins [ 22 ]. Indeed, other researchers who used various distillation methods for the extraction of garlic volatiles also found that organosulfur compounds such as DDS, diallyl trisulfide, and methyl allyl trisulfide were among the four most abundant ones [ 4 , 23 , 28 , 29 ]. In our study, DDS was also an important volatile constituent detected in percentages ranging from 1.81 to 8.55% (4.34 ± 1.47%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic dithiins are presumed to be the first products of allicin transformation, while acyclic compounds are produced during the thermal degradation of cyclic dithiins [ 22 ]. Indeed, other researchers who used various distillation methods for the extraction of garlic volatiles also found that organosulfur compounds such as DDS, diallyl trisulfide, and methyl allyl trisulfide were among the four most abundant ones [ 4 , 23 , 28 , 29 ]. In our study, DDS was also an important volatile constituent detected in percentages ranging from 1.81 to 8.55% (4.34 ± 1.47%).…”
Section: Resultsmentioning
confidence: 99%
“…Common garlic ( Allium sativum L., family Alliaceae) is the second most widely consumed bulb crop and one of the most cultivated bulb vegetables in Greece and worldwide, with an annual production of 28,494,130 tons and a total harvested area of 1,546,741 hectares [ 1 , 2 ]. It is consumed raw, cooked, or as an ingredient of herbal medicinal products and food supplements [ 3 , 4 ]. Garlic is considered effective and safe for the prevention and treatment of cardiovascular and other metabolic diseases, such as atherosclerosis, hyperlipidemia, thrombosis, hypertension, and diabetes; it also possesses antifungal, antibacterial, and antiviral properties and regulates blood sugar levels [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study (Figure 1), we demonstrated the modeling of resistant cells. Allium species are effective in the treatment of various diseases through their bioactive compounds, including sulfur compounds and polyphenols [20,21]. Notably, A. senescens is involved in suppressing cancer growth and development, it has anti-inflammatory and antioxidative activities, and contains bioactive compounds, such as allicin, alliin, antifungal activators [20,22], and polyphenols (hydroxycinnamic acids such as ferulic acid, p-coumaric acid, and phytosterols) [20].…”
Section: Discussionmentioning
confidence: 99%
“…The inestimable value of the Mediterranean agrobiodiversity, and its strong link with the MD and its beneficial effects on human health, are increasingly emerging due to the collaborative work of ethnobotanists, horticulturists, plant breeders, food chemists, and nutritionists, who together are recovering and generating new knowledge and genetic material, and are characterizing the nutritional and bioactive profile of many fruit and vegetable local landraces and wild edible species. Agrobiodiversity resources typical of the Mediterranean region, rich in bioactive compounds and commonly included as ingredients of the MD, are, for example, the multiple local landraces and selections of vegetables characterized by different shapes, harvest times, pigmentation, and associated nutritional and bioactive profiles [56,57], such as artichoke and cardoon [58][59][60][61][62][63], carrots [64][65][66], chicory and lettuce [67,68] among the Asteraceae family; broccoli and cauliflower [69] and kale [70] among the Brassicaceae family; cultivated and wild garlic [47,48,[71][72][73], and onion [50,[74][75][76] among the Liliaceae family; common beans, cowpea, fabae, and lentils among the Leguminosae family [77][78][79], melons and watermelons [80][81][82], or zucchini and squashes [83,84] among the Cucurbitaceae family; and tomato [85][86][87][88][89]…”
Section: Mediterranean Diet and Agrobiodiversitymentioning
confidence: 99%
“…These beneficial activities have been associated with the presence of specific compounds in plants that are commonly used in this dietary pattern, including phenolic compounds, such as hydroxycinnamic and chlorogenic acid [181], saponins [182], flavones and flavonoids [99,101,183,184], tannins [126], polysaccharides [185], glucosinolates [186,187], and other organosulfur compounds [71,188]. The mechanisms involved in the bioactive properties of MD ingredients against cancer have not yet been thoroughly revealed, however, it is hypothesized that they modify the expression of hormones and growth factors that induce cancer pathogenesis [12].…”
Section: Cancermentioning
confidence: 99%